1989
DOI: 10.1212/wnl.39.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral vasocapacitance and TIAs

Abstract: We report the vasocapacitance of the cerebral circulation, as determined by cerebral blood flow reactivity to induced hypercapnia using fluoromethane positron emission tomography, in 32 patients with unilateral anterior circulation transient ischemic attacks. A hemodynamic subset of eight patients, defined based on exertional, positional, orthostatic, or cardiac dysrhythmic induction of symptomatology, is characterized by multiple (median, 4.5 attacks per patient), brief (median, 2.5 minutes per attack), conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(26 citation statements)
references
References 0 publications
2
24
0
Order By: Relevance
“…Finally, the provocation of symptoms by orthostatic changes underscores the mechanism of perfusion failure, as proposed by Caplan and Sergay. 30 Thus, we believe that limb-shaking is probably a specific sign of border zone ischemia, a thesis supported by both PET findings in other patients 31 and by the specific clinical-hemodynamic correlations in our patient. The apparent rarity of orthostatic cerebral ischemia may reflect its underrecognition 32 or the special circumstances under which symptoms from low blood flow alone may occur.…”
Section: Discussionsupporting
confidence: 83%
“…Finally, the provocation of symptoms by orthostatic changes underscores the mechanism of perfusion failure, as proposed by Caplan and Sergay. 30 Thus, we believe that limb-shaking is probably a specific sign of border zone ischemia, a thesis supported by both PET findings in other patients 31 and by the specific clinical-hemodynamic correlations in our patient. The apparent rarity of orthostatic cerebral ischemia may reflect its underrecognition 32 or the special circumstances under which symptoms from low blood flow alone may occur.…”
Section: Discussionsupporting
confidence: 83%
“…17,18,36 -38 Although the anatomic presence of occlusion does not predict distal hemodynamic impairment, several retrospective studies of patients with carotid disease have found an association between 2 angiographic patterns of collateralization and reduced perfusion pressure: ophthalmic artery reconstitution of the internal carotid artery and retrograde pial collateralization. 11,[13][14][15]17,18 Neither these nor other prospectively recorded angiographic findings identified patients with increased OEF in the St Louis Carotid Occlusion Study. 10 Pial collateralization in the St Louis Carotid Occlusion Study was defined as retrograde MCA flow in any cortical vessel.…”
Section: Discussionmentioning
confidence: 95%
“…A proportion of patients with a recently symptomatic severe carotid stenosis or occlusion have diminished perfusion of the ipsilateral cerebral hemisphere and cannot increase perfusion in response to raised levels of carbon dioxide. 10 -24 Consistent results have been obtained from studies with transcranial Doppler ultrasound, 10 -13 single-photon emission computed tomography, 14 -16 positron emission tomography, 15,[22][23][24] and other imaging techniques. [17][18][19][20][21] Such patients also have metabolic changes in the affected hemisphere that are consistent with ischemia in the absence of any evidence of cerebral infarction.…”
mentioning
confidence: 78%